Coefficient Estimate Problem for a New Subclass of Biunivalent Functions. (28th October 2013) - Magesh, N.; Rosy, T.; Varma, S.
Abstract : We introduce a unified subclass of the function class Σ of biunivalent functions defined in the open unit disc. Furthermore, we find estimates on the coefficients | a 2 | and | a 3 | for functions in this subclass. In addition, many relevant connections with known or new results are pointed out.